The End of a 60-year Riddle: Identification and Genomic Characterization of an Iridovirus, the Causative Agent of White Fat Cell Disease in Zooplankton. Issue 4 (1st April 2018) - Toenshoff, Elena R; Fields, Peter D; Bourgeois, Yann X; Ebert, Dieter
Abstract: The planktonic freshwater crustacean of the genus Daphnia are a model system for biomedical research and, in particular, invertebrate-parasite interactions. Up until now, no virus has been characterized for this system. Here we report the discovery of an iridovirus as the causative agent of White Fat Cell Disease (WFCD) in Daphnia . WFCD is a highly virulent disease of Daphnia that can easily be cultured under laboratory conditions. Although it has been studied from sites across Eurasia for more than 60 years, its causative agent had not been described, nor had an iridovirus been connected to WFCD before now. Here we find that an iridovirus—the Daphnia iridescent virus 1 (DIV-1)—is the causative agent of WFCD. DIV-1 has a genome sequence of about 288 kbp, with 39% G+C content and encodes 367 predicted open reading frames. DIV-1 clusters together with other invertebrate iridoviruses but has by far the largest genome among all sequenced iridoviruses. Comparative genomics reveal that DIV-1 has apparently recently lost a substantial number of unique genes but has also gained genes by horizontal gene transfer from its crustacean host. DIV-1 represents the first invertebrate iridovirus that encodes proteins to purportedly cap RNA, and it contains unique genes for a DnaJ-like protein, a membrane glycoprotein and protein of the immunoglobulin superfamily, which may mediate host–pathogen interactions and pathogenicity. Our findings end a 60-year search for the causative agent of WFCD and add to our knowledge of iridovirus genomics and invertebrate–virus interactions.